Spikes em espectrometria alfa para analise de amostras geologicas - Bonotto, Daniel Marcos [UNESP] (My University, 1990)
The technique of isotope dilution has been extensively utilized for determining the content of trace elements in geological samples; it has been especially useful for the determination of 238U and 234U contents in crustal materials with measurements made by alpha spectrometry. 232U-228Th has usually been used as diluent (spike) during the application of this analytical technique. More recently, 236U and 229Th have been used. Some methodological problems concerning the utilization of these spikes are presented with examples of experimental data obtained in analyses of groundwater and borehole spoil samples from Morro do Ferro, Pocos de Caldas (MG). -from English summary
The use of the alpha spectrometry technique in geological samples analysis
Keywords: alpha spectrometry; geochemical analysis; isotope dilution technique; uranium; Brazil, Minas Gerais, Pocos de Caldas, Morro de Ferro